Retinal Vascular Disease - Joussen, A.M; Gardner, T.W; Kirchhof, B.; Ryan, S.J (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Vascular diseases of the retina are a major cause of blindness among all age groups. Edited and written by internationally well-known experts, this state-of-the-art comprehensive overview of basic and clinical science will enhance the understanding of retinal vascular disease and help in the evaluation of current and future treatment approaches for the clinician. The well-structured and highly illustrated text is divided into the following three main sections: Pathogenesis of retinal vascular disease General concepts in the diagnosis and treatment of retinal vascular disease Pathology, clinical course and treatment of retinal vascular disease Reader-friendly through: Step-by-step explanation of all treatment procedures Richly illustrated by clinical image series including illustrated single case follow-up This unique textbook-atlas also includes topics which are not currently found in other retinal disease textbooks, such as case reports and clinical follow-ups. General ophthalmologists, retina specialists as well as ophthalmologists in training will find this book highly stimulating and useful for their daily practice.